Hello
To solve this question, we were given a particular function and asked to evalute when the function is defined with a particular variable
![\begin{gathered} f(x)=3-4x \\ g(x)=3x+4x^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lxwwa6atxownagr0d7iv0dfxl33lz0cg4r.png)
For f(-6)
![\begin{gathered} f(x)=3-4x^{} \\ f(-6)=3-4(-6) \\ f(-6)=3-4(-6) \\ f(-6)=27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j0dlvvusae4e5clyymynn3nc67ke3i62oe.png)
For g(-9)
![\begin{gathered} g(x)=3x-4x^2 \\ g(-9)=3(-9)+4(-9)^2 \\ g(-9)=297 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wmq54s8v74j3sfknavtlv3uv1q5ew2erlc.png)
For f(-9) + g(-9)
![\begin{gathered} f(x)=3-4x \\ g(x)=3x+4x^2 \\ f(-9)+g(-9)=3-4(-9)+3(-9)+4(-9)^2=336 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cmkybpw8lvh8n30neobhpqr9tds4ll5en5.png)
for g(-6) - f(-9)
![\begin{gathered} g(x)=3x+4x^2 \\ f(x)=3-4x \\ g(-6)-f(-9)=3(-6)+4(-6)^2-(3-4(-9))=87 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/11pu8kr9ls7sw0c1zco3t4epqgy2g96t55.png)
For f(-9).g(-7)
![\begin{gathered} g(x)=3x+4x^2 \\ f(x)=3-4x \\ f(-9).\text{g}(-7)=3-4(-9)*3(-7)+4(-7)^2=39*175=6825 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lgq6lrgnylgr6xosxkxo7sycu2mztkfxk8.png)
For f(-6) / g(-7)
![\begin{gathered} f(x)=3-4x \\ g(x)=3x+4x^2 \\ (f(-6))/(g(-7))=(3-4(-6))/(3(-7)+4(-7)^2)=(27)/(175) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s0p6r0j4awt08eu8gkh27wfbsh6rdjey0b.png)
From the calculations above, i believe you must've seen your mistaken and taken the necessary correction.
Therefore the answers are
1 = 27
2 = 297
3 = 336
4 = 87
5 = 6825
6 = 27/175